NASKAH RONTAL DARUL SAMAR Sebuah Naskah Sasak Bernuansa Keagamaan Islam - Moh Amaluddin (Analisa: Journal of Social Science and Religion, 2008)
This palmistry palm manuscript contents various Islamic thoughtson faith, syariat, and tasawuf. In faith area, Islamic thoughts includedorder on Allah Substances and on value of human being acts. In syariatarea, it included immediateness to do matrimonial function, on the goodand the bad months to carry out marriage. In tasawuf area, it includedIslamic thoughts on nature of our body, on sincerity and surrendering toAllah, on endeavors to achieve bright mind, on meaning behind the caution given after death. on searching of supernatural experiences, onkinds of religious knowledge.